Lattice for Rough Intervals - Dipankar Rana; Sankar Kumar Roya (Journal of New Results in Science)
This paper deals with the rough interval approach onlattice theory. In the interval-set model, a pair of sets is referredto as the lower and upper bounds which define a family of sets. Asignificant difference between these concepts lies in the definitionand interpretation of their extended set-theoretic operators. Theoperators in the rough-set model are not truth-functional, whilethe operators in the interval-set model are truth-functional. Wehave showed that the collection of all rough intervals in an approximation space forms a distributive lattice. Some important resultsare also proved. Finally, an example is considered to illustratedthe paper